PANCYTOPENIA IN TWO NATIONAL ETHNIC GROUPS OF BALUCHISTAN - Tareen, Saleh Muhammad; Bajwa, Masroor Ahmad; Tariq, Mohammad Masood; Babar, Shakeel; Tareen, Abdul Malik (Journal of Ayub Medical College Abbottabad, 2011)
Background: Pancytopenia is a recognisable haematological problem with common categorises diagnosis but best possible diagnostic approach is still to be defined. Objective: The aim of this study was to determine the frequent causes and clinical presentation of pancytopenia in relation to age and sex in different ethnic groups of two national (Pakistani and Afghan) living in Baluchistan province. Methods: This is a cross sectional descriptive type of study was carried out on patients (n=180) for two years (July 2009-June 2011). Cases were successively registered in 2 provincial government hospital and 2 private clinics in Quetta with diagnosis of pancytopenia. Results: The most frequent causes of pancytopenia in both national ethnic groups were malaria (29.44%) fallowed by tuberculosis (17.22%), leukaemia (16.67%), aplastic anaemia (13.33%), hepatitis (12.22%), other diseases (7.22%) and iron deficiency anaemia (3.89%). Overall, 63.89% male subjects were observed pancytopenia as compared to 36.11% female patients. The results also showed that patients with age >41 years were highly (50%) affected by pancytopenia followed by 21-40 years (30.66%) and <20 years (19.44%). Moreover, leukaemia cases were observed significantly higher in Afghan subjects (>41 years). The most common symptom of patients was (71.11%) fever followed by Pallor (42.22%), fatigue (38.33%), weight loss (26.11%) and dizziness (25.56%). Leukaemia and aplastic anaemia were found to be the most serious causes of pancytopenia in Afghan ethnic group. Conclusions: Malaria, tuberculosis, aplastic anaemia, and leukaemia were the leading causes of pancytopenia in Pakistani and Afghan ethnic groups. Severe pancytopenia has significant relation with the clinical conclusion and can be used as a prognostic marker. Keywords: Pancytopenia, Ethnic groups, Malaria, Tuberculosis, Leukaemia